The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/ncomms9418
|View full text |Cite|
|
Sign up to set email alerts
|

Macroscopic ordering of helical pores for arraying guest molecules noncentrosymmetrically

Abstract: Helical nanostructures have attracted continuous attention, not only as media for chiral recognition and synthesis, but also as motifs for studying intriguing physical phenomena that never occur in centrosymmetric systems. To improve the quality of signals from these phenomena, which is a key issue for their further exploration, the most straightforward is the macroscopic orientation of helices. Here as a versatile scaffold to rationally construct this hardly accessible structure, we report a polymer framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 56 publications
1
51
0
Order By: Relevance
“…The bold trace at Tc = 88°C marks the phase transition between two square columnar phases. In both phases reflections indexed as (10), (11), (20) etc. are seen, their q 2 ratio being 1:2:4:5 ….…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bold trace at Tc = 88°C marks the phase transition between two square columnar phases. In both phases reflections indexed as (10), (11), (20) etc. are seen, their q 2 ratio being 1:2:4:5 ….…”
Section: Resultsmentioning
confidence: 99%
“…Among numerous well established or developing applications of liquid crystals (LC) is nanoscale patterning on the sub-10 nm length scale. 1 , 2 Such patterning may be used in organic electronics and photovoltaics, 3 , 4 , 5 , 6 , 7 , 8 in selective membranes, 9,10,11 for ion conducting arrays 12, , 13 , cubosomes 14 and hexosomes 15 for drug delivery etc. For use in soft nanolithography highly ordered arrays are required, preferably with a square or rectangular lattice and high dimensional stability, ideally with zero thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed structure of the crosslinked polymer based on these data is given in (b‐i). Reproduced with permission . Copyright 2015, Nature Publishing Group.…”
Section: Macroscopically Oriented Crosslinked Porous Polymers From Lcsmentioning
confidence: 99%
“…As described in Section , one notable advantage of porous crosslinked polymers, compared with other conventional porous materials, is the ease with which chiral structures can be introduced. In 2015, Ishida and co‐workers demonstrated that chiral pores can be rationally constructed by using chiral template units in this synthetic scheme, and they reported on a macroscopically oriented version (Figure b). In their studies, an enantiopure amine [(1 R ,2 S )‐norephedrine; (–)‐(1 R ,2 S )‐2‐amino‐1‐phenyl‐propan‐1‐ol] was used as a template unit, whereas the same frame unit as described in Section and , the wedge‐shaped benzoic acid with three acryloyl groups (Figure bi, left), was used as its counterpart.…”
Section: Macroscopically Oriented Crosslinked Porous Polymers From Lcsmentioning
confidence: 99%
See 1 more Smart Citation